Phonation Duration and Optimum Frequency - Nataraja NP (Journal of All India Institute of Speech and Hearing, 1970)
Optimum frequency is  considered to be  the frequency at which maximum physio-acoustic economy is achieved. The purpose of  this  study was to find out  the acoustic economy,  at optimum frequency,  as determined by an objective  method  of  locating optimum frequency.The  acoustic  economy was measured in terms of the maximum duration for which the subjects could sustain phonation at a particular  frequency. The maximum phonation duration at optimum and at frequencies higher and lower than the optimum frequency were measured using a stop-watch.15 male and 15 female adults were asked to phonate vowel /a/ as long as possible keeping the frequency  and intensity constant. The  maximum phonation duration at optimum, + 100 Hz, + 200 Hz, + 50  Hz  and - 50 Hz from the  optimum were determined. The results showed  that the maximum phonation duration  at  optimum  frequency  was significantly longer than at other frequency levels. Therefore it was considered that  there was maximum acoustic economy at  optimum frequency,  as determined  by  this method.